Using New Vaginal Doses Evaluation System to Assess the Dose–Effect Relationship for Vaginal Stenosis After Definitive Radio(Chemo)Therapy for Cervical Cancer - Wang, Juan; Zhang, Kai-shuo; Liu, Zi; Wang, Tao; Wang, Rui-hua; Zhang, Fu-quan; Yu, Lang; Wang, Ya-li; Wei, Li-chun; Shi, Mei; Li, Sha; Liu, Bao-gang; et al. (Frontiers in Oncology, 2022)
Objective: To identify the relationship between vaginal doses and vaginal stenosis (VS) using PIBS points and the ICRU-R evaluation system for definitive radio(chemo)therapy in locally advanced cervical cancer. Methods and Materials: From a vaginal dose study in China, 351 patients were prospectively assessed. For every reference point of the PIBS system and ICRU-R, parameters were calculated for all BT and summed with EBRT. Pearson’s chi-square test and Student’s unpaired t-test compared variables with and without vaginal stenosis (VS) G≥2. The risk factors were assessed for VS G≥2 in multi- and univariate analyses through Cox proportional hazards model followed by a dose-effect curve construction. The VS morbidity rate was compared via the log-rank test using the median of vaginal reference length (VRL). Results: The patients (38-month median follow-up) had 21.3% three-year actuarial valuation for VS G≥2. Compared to G<2 patients, VS G≥2 patients received higher doses to PIBS points except for PIBS-2 and had significantly shorter VRL. VRL (HR=1.765, P=0.038), total EBRT and BT ICRU-R point dose (HR=1.017, p=0.003) were VS-associated risk factors. With VRL >4.6 cm, the 3-year actuarial estimate was 12.8% vs. 29.6% for VRL ≤4.6 cm. According to the model curve, the risk was 21%, 30%, and 39% at 75Gy, 85Gy, and 95Gy, respectively (ICRU-R point dose). Conclusions: PIBS system point doses correlated with late vaginal toxicity. VRL combined with both EBRT and BT dose to the ICRU-R point contribute to VS risk.